Research on the Application of Online and Offline Mixed Teaching Mode of Marketing Course Based on the BOPPPS Model - Huang, Chih-Hsuan; Li, Li; Liu, Cuiyun; Yao, Jingyi; Li, Xiumei (International Journal of Humanities and Education Development (IJHED), 2023)
BOPPPS teaching fully integrates the advantages of online self-study and offline courses. This kind of teaching has been widely used in college education, and has proved to have a positive effect on improving students’ ability to solve problems. It also has a significant effect on improving students’ sense of self-efficacy, stimulating learning interest and improving their ability to learn independently in practice. During the implementation of the research, the team explored and practiced the online and offline mixed teaching mode of marketing course with the wisdom tree teaching platform, and built teaching resources for students to learn and discuss on their own, which is a reference for future online mixed teaching.